Atividades de gestão em comunidades terapêuticas no Maranhão - RIBEIRO, Flávia Cristiane Mouzinho Silva (2020)
In 2019 there were significant changes in public drug policy in Brazil. Undoubtedly one of the most controversial was the financing of the Therapeutic Communities (TCs) as a modality of assistance to harmful users and dependents of chemical substances. These institutions have existed for more than 50 years in Brazil and have a controversial and controversial history. At the same time that its legal framework for regulation is recent and, as never before, it has been on the Federal Government's agenda. This work has the research problem to understand how the managers of these institutions are dealing with the changes implemented by the new legislation and what is the impact on their activities in their daily work. 10 managers of 04 Therapeutic Communities in the State of Maranhão were interviewed, who are looking to receive public funding, aiming to understand the activities and the meanings of the work. It is a field research with qualitative classification from which it was possible to hear the managers who are at the tip of the execution of this process and understand how this has happened in institutions in Maranhão. The outcome pointed to a sense of mission and religious vocation as the biggest motivator for carrying out this work. But they were not only in religiosity, as they received the legislation in a positive way, seeing it as a way of improving their institutions, professionalizing their work activities and, finally, having a place within public policy. It was observed that the TCs face many challenges, as there is still a gap between the publication of the laws, complete adaptation of the institutions and the implementation, especially with regard to the arrival of the resource.